Assessment of soil degradation in Pitu District, Ngawi Regency - M Mujiyo; S Sumarno; S Sudadi; Retno Wisnu Murti (Brawijaya University, 2020)
This study aimed to determine the status of soil damage in Pitu District, Ngawi Regency. The study was conducted in a descriptive exploratory with survey methods. Determination of site sampling was done by purposive sampling, based on distribution or division and land use categories from the results of map overlays. Assessment of soil degradation potency was based on land units from the uniformity of the soil, rainfall, slope, and land use map. Land units resulting from overlay were scored based on the results of multiplication of weights and soil, slope, rainfall, and land use ratings. Total score indicates soil Degradation Potency (SDP). Assessment of soil degradation status was done through matching and scoring. Field observation results were matched with the standard criteria of soil degradation from Indonesian Government Regulation No. 150 of 2000. Each parameter was scored, then the total score was used to determine soil degradation status. Soil degradation potency in Pitu District, Ngawi Regency is PR II (Low) at LMU (Land Map Units) 1, 3, 4, 5, and 8, and PR III (Moderate) at LMU 2, 6, 7, 9, and 10. Soil degradation status in Pitu District, Ngawi Regency is slightly degraded at all LMU, with limiting factors, namely texture, bulk density, total porosity, and permeability.